EXPERT SYSTEMS to diagnose cancer SKIN USING MICROSOFT VISUAL BASIC 6.0 - Asrie Asrie (Jurnal Sistem Informasi, 2007)
The growing world of computer technology so that all the problems can be solved one of them is by making "Expert System for Diagnosing Skin Cancer" in which the expert system, we can diagnose the complaint that we experience without having to go out for medicine. This expert system is designed with the view that attention to simplicity in the operation.